Analisis Pengaruh Brand Image dan Harga terhadap Keputusan Pembelian Konsumen (Studi pada Produk Fashion Online) - Mandasari, Puti; Machmud, Pajar (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
This study aims to analyze the influence of brand image and price on consumer purchasing decisions for online fashion products. The research method used a quantitative approach with a survey technique through the distribution of questionnaires to 120 respondents who had purchased fashion products through e-commerce platforms. Data analysis was performed using multiple linear regression using SPSS software. The results show that brand image has a positive and significant effect on consumer purchasing decisions, while price also has a positive but lower influence than brand image. The combination of the two explains 62.4% of the purchasing decision variable. This study emphasizes the importance of company strategies in building a strong brand image and setting competitive prices to increase consumer purchasing interest in the online fashion market.